Commercial Pharmacogenetic Tests in Psychiatry: Do they Facilitate the Implementation of Pharmacogenetic Dosing Guidelines? - Fan, Mikayla; Bousman, Chad A. (Pharmacopsychiatry, 2019)
Introduction Expert groups have created dosing guidelines to facilitate the implementation of pharmacogenetic knowledge into clinical practice and commercial pharmacogenetic tests are becoming increasingly accessible. However, the extent to which these commercial tests facilitate the implementation of dosing guidelines is not clear.Methods Gene-drug pairs included on 22 commercial pharmacogenetic test panels were extracted and cross-referenced with the 74 gene-drug pairs with dosing guidelines in the Pharmacogenetics Knowledgebase, with particular attention given to the 28 gene-drug pairs relevant to psychiatry.Results On average, 70% of the 28 gene-drug pairs most relevant to psychiatry were covered by the examined tests. Six gene-drug pairs (CYP2D6-venlafaxine, CYP2D6-paroxetine, CYP2D6-amitriptyline, CYP2C19-sertraline, CYP2C19-citalopram, CYP2C19-amitriptyline) were included by all tests. Gene-drug pairs included on less than half of the test panels included HLA-B-phenytoin (14%), HLA-A-carbamazepine (24%), HLA-B-carbamazepine (29%), and CYP2D6-zuclopenthixol (43%).Discussion Most commercial pharmacogenetic tests we examined are well-equipped to facilitate implementation of the majority of dosing guidelines relevant to psychiatry but are limited in their ability to facilitate implementation of the full spectrum of dosing guidelines currently available.
Keywords: decision support tools; gene-drug interaction; translation